Wnt2 complements Wnt/β-catenin signaling in colorectal cancer - Jung, Youn-Sang (Oncotarget, 2015)
Wnt2 is implicated in various human cancers. However, it remains unknown how Wnt2 is upregulated in human cancer and contributes to tumorigenesis. Here we found that Wnt2 is highly expressed in colorectal cancer (CRC) cells. In addition to co-expression of Wnt2 with Wnt/β-catenin target genes in CRC, knockdown or knockout of Wnt2 significantly downregulates Wnt/β-catenin target gene expression in CRC cells. Importantly, depletion or ablation of endogenous Wnt2 inhibits CRC cell proliferation. Similarly, neutralizing secreted Wnt2 reduces Wnt target gene expression and suppresses CRC cell proliferation. Conversely, Wnt2 increases cell proliferation of intestinal epithelial cells. Intriguingly, WNT2 expression is transcriptionally silenced by EZH2-mediated H3K27me3 histone modification in non-CRC cells, However, WNT2 expression is de-repressed by the loss of PRC2's promoter occupancy in CRC cells. Our results reveal the unexpected roles of Wnt2 in complementing Wnt/β-catenin signaling for CRC cell proliferation.